Public management communication strategy in managing accessibility of public services for persons with disabilities in Serang city - Saepudin, Eli Apud; Hartoko, Gatot; Zulfikar, Meiby; Priatna, Achmad Nashrudin; Arasid, Mohamad Ikrom (Trigin Publisher, 2024)
Communication strategies are key in dealing with complex challenges rooted in historical, social and regulatory factors. Stigma and discrimination, low understanding of the needs of people with disabilities, non-comprehensive regulations, budget and infrastructure limitations, lack of coordination and collaboration, and cultural and social challenges are the main obstacles in realizing inclusive accessibility. The method in this research is a qualitative descriptive approach. The purpose of this research is to examine the background of these problems and identify potential solutions to improve the accessibility of public services for people with disabilities in Serang City. Comprehensive and sustainable solutions are needed to address the root causes and build an inclusive city for all.